Chapter Balancing Between Smart and Inclusive: Learning Cities for Sustainable Urban Communities - Nemèth, Balàzs (Studies on Adult Learning and Education, 2023)
Since 2012, Global Learning Cities has become a successful network-based movement of UNESCO which demonstrates not only linkages, but also dependencies amongst community development, adult learning and active citizenship (UNESCO 2017). Examples of Cork, Espoo, Belgrade and South Korea have highlighted (Németh 2020), that communities are unable to develop successful models of learning cities unless they combine smart, creative and sustainability dimensions through community-based adult and lifelong learning for social cohesion, economic stability, growth and environmental awareness. Equitable ways of community learning can better reach underrepresented groups of adults who want to develop and sustain their neighbourhoods through collecting and sharing knowledge (Ó Tuama 2020). Other examples from India, Palestine and the UK demonstrate that it is not the label itself, but the smart and creative urban adult learning which can be combined with needs of communities (Németh et al. 2020). In the evolution of learning cities, we have arrived to an Era of uncertainties, therefore, we have to demonstrate that the learning cities depend on better participation, performance and partnerships in learning, surrounded by collective actions for better futures of education.